SETS VISION: HOW TO DEVELOP STUDENTS’ CLIMATE LITERACY THROUGH PHYSICS LEARNING? - ERI EKAYANTI, NOVIA; HARIYONO, EKO (Inovasi Pendidikan Fisika, 2020)
Climate change is a severe global problem. The impact of climate change is widespread in all countries, including in Indonesia. Lack of public awareness of climate change is one of the causes of climate change getting out of control. One way of improving public awareness is to develop society?s climate literacy through students at school. Starting from this problem, the researcher offered an innovation in physics learning with the SETS (Science, Environment, Technology, and Society) vision on global warming material as a solution to develop students climate literacy. This research aims to develop students? climate literacy through SETS vision learning. This quantitative research with quasi-experimental design and non-equivalent control group design. The subjects in this research were class XI MIA 5 and XI MIA 8. The data analysis method used is the test method consists of pre-test and post-test. Climate literacy ability was analyzed using paired t-test and gain index. The results showed that the climate literacy ability of students after applying the SETS vision has increased higher than the class with regular teaching. The n-gain score of students? climate literacy in the experimental class was 0.70 classified as a high category while in the control class was 0.44 classified as a moderate category. Based on the results of the research, it conclude that the SETS vision was learning able to develop climate literacy of students on global warming material. Climate-literate students will have awareness and concern about climate change that occurs in the surrounding environment.